PH‐Regulated Heterostructure Porous Particles Enable Similarly Sized Protein Separation. Issue 16 (27th February 2019) - Song, Yongyang; Fan, Jun‐Bing; Li, Xiuling; Liang, Xinmiao; Wang, Shutao
Abstract: Porous particles are frequently used for various healthcare applications that involve protein separation processes. However, conventional porous particles, either homogeneous particles or those subjected to surface modification with a layer of specific molecules, often encounter bottlenecks in separating proteins with similar size. Here, it is reported that heterostructure‐enabled separation particles (HESP), synthesized by a double emulsion interfacial polymerization process, can effectively and rapidly separate similarly sized proteins. Double emulsion interfacial polymerization endows the HESP with a nanoscale carboxylic layer outside the particles and inside the pores, allowing pH‐regulated selective adsorption of proteins. Thus, by optimizing the environmental pH, proteins with similar size can be effectively and rapidly separated. These HESP are expected to show potential in widespread applications ranging from biomolecule adsorption, encapsulation, and separation to controlled release and other biomedical fields. Abstract : Heterostructure porous particles synthesized by double emulsion interfacial polymerization can successfully separate proteins with similar size. Double emulsion interfacial polymerization endows the particles with a nanoscale carboxylic layer outside the particles and inside the pores, allowing pH‐regulated adsorption of proteins. Optimizing the environmental pH can enable the effective separation of proteins with similar size in a short time.